Analisa Perbandingan Network File System (Nfs) Dan Samba Sebagai File Sharing Menggunakan Linux Ubuntu - Pradana, Muhammad Dian, Dr. Ir. Bana Handaga, M.T (2015)
This study describes the comparison of file sharing system between the Network File System (NFS) and Samba. To achieve the goal, the two systems are used in the Linux operating system Ubuntu with a different computer specifications. The positioning of the system is placed in a different computer. So, requires two computer servers as a second installation of the system. Systems that have undergone the installation process, then performed the process of sharing files from a folder that has been prepared. The difference of the two systems in terms of speed and ease of use. In terms of speed, the Network File System (NFS) is superior to Samba. While ease of use, Samba has a plus because the system has a Graphic User Interface (GUI) that allows the network administrator to set / configure. In the file size of 679.5 MB, the average speed of a computer system using NFS is client-1 57.807seconds and client-2 57.794 seconds while the system is Samba there is client-3 76.173 seconds and client-4 75.378 seconds. At 2.9 GB sized files, the average speed of a computer system using NFS is a client-1 244 587 and the second client-2 244.22 seconds while the system Samba client-3 316.115 seconds and client-4 320.199 seconds.